1994
DOI: 10.1121/1.408460
|View full text |Cite
|
Sign up to set email alerts
|

Jet formation and jet velocity fluctuations in a flue organ pipe

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 0 publications
0
38
0
Order By: Relevance
“…The details of the determination of these parameters were discussed by Verge et al 3 In the same paper, the flue exit was shown to be a volume source which acts as a sound source when the jet velocity U j fluctuates. This effect appears to be very important during the attack transient since it provides, in combination with the initial interaction of the jet with the labium, the signal that triggers the attack transient.…”
Section: The Basic Modelmentioning
confidence: 94%
See 2 more Smart Citations
“…The details of the determination of these parameters were discussed by Verge et al 3 In the same paper, the flue exit was shown to be a volume source which acts as a sound source when the jet velocity U j fluctuates. This effect appears to be very important during the attack transient since it provides, in combination with the initial interaction of the jet with the labium, the signal that triggers the attack transient.…”
Section: The Basic Modelmentioning
confidence: 94%
“…As was discussed by Verge et al, 3 this representation enables one to take into account the effects of the jet velocity variations due to pressure fluctuations at the flue exit. At the flue exit, the mass conservation law can be applied where Q j , Q out, and Q in are the jet flow and the flow in the portion ␦ out and ␦ in of the mouth end correction, respectively.…”
Section: The Basic Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…Passive response of the pipe The description of the recorder is based on an acoustic model adapted from works of Verge 22 and Chaigne. 23 The geometry of the recorder permits a one-dimensional model.…”
Section: Simplified Modelmentioning
confidence: 99%
“…In fact, in steady blowing conditions, models not taking into account this effect (e.g. in [11]) led to an overestimation of the amplitude of the pressure oscillation in the pipe (see for example [17]). Therefore, as in [20], we have taken into account these interactions jet/labium, but as already mentioned, the system we are studying is different : the resonator's length is time-varying, controlled through the piston mechanism and there is no finger hole (see Fig.…”
Section: Introductionmentioning
confidence: 99%